Pengaruh Kota Satelit BSB dan Kampus UIN Walisongo Terhadap Perkembangan Koridor Prof. Hamka Semarang - Shofiyah Nurmasari; Faiqoh Roshwah Salsabila; Haidar Tamimi Mustofa (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2021)
Prof. Hamka corridor is the main strategic corridor in Ngaliyan Semarang. In the south of the corridor, there is a BSB Satellite City and along the corridor, there is the UIN Walisongo campus. Prof. Hamka corridor is a dense and rapidly growing corridor with the presence of 2 magnets in this area. This study aims to analyze the effect of the growth and development of the Prof Hamka corridor in Semarang with the presence of 2 magnets in the area based on Hamid Shirvani's theory. The method used is the descriptive qualitative method. From the results of the analysis, it is known that the UIN Walisongo Campus and the BSB Satellite City have become magnets for various activities and have an influence on the growth and development of the area including changes in Land Use, Building Form, and Mass, Circulation and parking, Pedestrian ways, Signages, Open Space and Activity Support in the Prof. Hamka Corridor.